ROLE OF THE TOPIC BACTERIAL LYSATES IN THE PEDIATRIC PRACTICES - L.R. Selimzyanova (Педиатрическая фармакология, 2009)
The recurrent and chronic infections are an actual problem in pediatrics. The regular use of antibiotics leads to the resistance of the oral cavity pathogens and disturbances in the normal microflora balance. Bacterial lysates are considered to be the efficient means to prevent and treat the acute and chronic respiratory diseases. The article is an executive summary of literature on the bacterial immune response modulating agents, including the description of the mechanism of action of these medications. The article provides for the information on the peculiarities of the topic bacterial lysates.Key words: children, acute respiratory infections, chronic pharyngitis, chronic tonsillitis, stomatitis, bacterial immune response modulating agent.